Bridging Theories and Practice: Organizational Management in an Indonesian School Context - Velly Syafriani; Nuryasni; Tri Yuliani (Global Review of Tourism and Social Sciences, 2025)
This study examines the organizational management practices at UPTD SMP Negeri 2 Lareh Sago Halaban, focusing on leadership, human resource management, curriculum development, financial management, infrastructure maintenance, and community engagement. Using a qualitative descriptive approach, the research relies on secondary data from books, journals, and official documents. The findings reveal the integration of classical, neo-classical, and modern management theories, enabling the school to maintain structured operations while fostering adaptability and collaboration. Leadership and decision-making are pivotal in directing staff and ensuring alignment with educational objectives. Effective resource management and community engagement further enhance the institution's ability to navigate challenges and optimize performance. This study contributes theoretically by highlighting the interplay of organizational theories in educational settings and offers practical insights for improving school management. Limitations include reliance on secondary data and a single-case focus, suggesting future research expand scope and incorporate primary data collection.